Kepemimpinan Transformasional, Budaya Organisasi, Dan Motivasi Kerja Dalam Meningkatkan Kinerja Pegawai Pada Instansi Pemerintah - Gea, Ricardo Roh Zamaeri; Zebua, Dermawan (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to analyze the role of transformational leadership, organizational culture, and work motivation in improving employee performance at the Gunungsitoli Idanoi District Office. The novelty of this study lies in the qualitative approach that deeply explores the managerial dynamics in the public sector, which has different characteristics from the private sector. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation studies. Research informants were selected using a purposive sampling technique involving leaders and employees of the Gunungsitoli Idanoi District Office. The results of the study indicate that transformational leadership is able to encourage employee engagement, a strong organizational culture creates a conducive work environment, and work motivation plays an important role in improving employee performance. These findings provide practical implications for human resource management at the Gunungsitoli Idanoi District Office as well as theoretical contributions to the development of public sector management studies.